Impact of a mass media campaign on participation rates in a National Bowel Cancer Screening Program: a field experiment. Issue 1 (25th January 2019) - Durkin, Sarah J; Broun, Kate; Spittal, Matthew J; Wakefield, Melanie A
Abstract : Objectives and design: This field experiment aimed to compare bowel cancer screening participation rates prior to, during and after a mass media campaign promoting screening, and the extent to which a higher intensity campaign in one state led to higher screening rates compared with another state that received lower intensity campaign exposure. Intervention: An 8-week television-led mass media campaign was launched in selected regions of Australia in mid-2014 to promote Australia's National Bowel Cancer Screening Program (NBCSP) that posts out immunochemical faecal occult blood test (iFOBT) kits to the homes of age-eligible people. The campaign used paid 30-second television advertising in the entire state of Queensland but not at all in Western Australia. Other supportive campaign elements had national exposure, including print, 4-minute television advertorials, digital and online advertising. Outcome measures: Monthly kit return and invite data from NBCSP (January 2012 to December 2014). Return rates were determined as completed kits returned for analysis out of the number of people invited to do the iFOBT test in the current and past 3 months in each state. Results: Analyses adjusted for seasonality and the influence of other national campaigns. The number of kits returned for analysis increased in Queensland (adjusted rate ratio 20%, 95% CI 1.06% to 1.35%, p<0.01) during the months of the campaign and up to 2 months after broadcast, but only showed a tendency to increase in Western Australia (adjusted rate ratio 11%, 95% CI 0.99% to 1.24%, p=0.087). Conclusions: The higher intensity 8-week television-led campaign in Queensland increased the rate of kits returned for analysis in Queensland, whereas there were marginal effects for the low intensity campaign elements in Western Australia. The low levels of participation in Australia's NBCSP could be increased by national mass media campaigns, especially those led by higher intensity paid television advertising.